REKONSTRUKSI POLITIK PENDIDIKAN ISLAM: MENGATASI DIKOTOMI ILMU MELALUI KEADABAN PANCASILA - Ahmad Syukron (PT. IHLAS (Ilmu Adalah Segalanya) - BICARA CENTRE, 2026)
This study examines the reconstruction of Islamic education politics in Indonesia to address the persistent dichotomy between religious and general sciences, which has hindered the development of holistic and competitive human resources. The research aims to formulate a systematic and integrative model of Islamic education politics based on Pancasila civility as a strategic framework for achieving the vision of Indonesia Emas 2045. This study employs a qualitative approach using library research, drawing on primary sources such as national education policies and secondary sources including recent scholarly literature on Islamic education, moderation, and curriculum integration. Data were analyzed through qualitative content analysis involving thematic categorization, coding, and triangulation. The findings reveal that the dichotomy of knowledge, weak integration of Pancasila values, and the rise of intolerance constitute the core challenges in current Islamic education. In response, this study proposes a reconstruction model consisting of three main pillars: epistemological integration, internalization of Pancasila civility values, and methodological transformation toward student-centered learning. The study also formulates a multilevel implementation strategy and a phased roadmap for 2025–2045. The results indicate that this model has strong conceptual feasibility and relevance in fostering moderate, integrative, and globally competitive graduates. This study contributes to the development of an integrative paradigm of Islamic education that aligns religious values with national ideology, thereby strengthening both spiritual character and civic responsibility in contemporary Indonesia.